PKM PELATIHAN PENINGKATAN PENGETAHUAN REMAJA PUTERI TENTANG KESEHATAN REPRODUKSI DI SEKOLAH DASAR INKAM KABUPATEN KAMPAR TAHUN 2021 - Nislawaty; Fitri Handayani; Putri Ayuni (COVIT (Community Service of Health), 2022)
Adolescence is the most complex stage of life, both for adolescents themselves and their parents. During this period, children tend to take on new responsibilities and learn to be independent. This is also a good time for teenagers to be more responsible for their reproductive health. The importance of reproductive health for adolescents is because the response from the community to the need for reproductive knowledge is very low. Knowledge for teenagers must help them in living their lives to be more mature. Based on a preliminary survey conducted at the INKAM Elementary School of 10 female students who were interviewed, there are 8 students who do not know how to care for reproductive organs properly and correctly, while 2 of them know but the information is obtained from the internet. The purpose of implementing Community Service at INKAM Elementary School is to increase the knowledge of young women about reproductive health through outreach activities, and empowering accompanying teachers in providing regular education regarding the care of adolescent reproductive organs and things to watch out for. The method used is illustrative lectures and demonstrations. The result of this activity is an increase in adolescent knowledge about reproductive health and how to take care of reproductive organs. Suggestions that can be conveyed to the education sector is to make learning about reproductive devils an important subject, so that young women can keep their reproductive organs healthy and clean and they can be responsible for their reproductive organs. Keywords: Training, Knowledge Improvement, Reproductive Health